METODE PENDIDIKAN AKHLAK DALAM MEMBENTUK PERILAKU SOSIAL SISWA DI MADRASAH TSANAWIYAH NW MONTONG MAS - Nurhidayah, Nurhidayah; Komaruddin, Komaruddin; Sulistio, Iwan (SINERGI : Jurnal Riset Ilmiah, 2025)
Moral education is a very important aspect in shaping students' social behavior so that they are able to interact properly both in the school environment and in society. However, in reality, many students still lack good interaction within their environment. At MTs NW Montong Mas, various moral education methods have been implemented in daily life. This research aims to find out the methods of moral education applied at MTs NW Montong Mas in shaping students‟ social behavior, as well as the supporting and inhibiting factors involved.This study uses a qualitative descriptive approach with data collection techniques such as observation, interviews, and documentation. The subjects of the research included Islamic creed and morals teachers, guidance and counseling teachers, and students. The results of the study show that the methods of moral education used include role modeling, habituation, advice, and discipline. Supporting factors in the implementation of moral education in shaping students' social behavior include the commitment of teachers and school staff, student obedience, the supervision system, and consistent coaching, as well as support from families and an Islamic social environment. The inhibiting factors include lack of facilities, inconsistency in implementing methods, students who are not aware yet, lack of student response to guidance, the influence of social media, and peer environments outside of school